2022
DOI: 10.1039/d2cp00673a
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Pt–OH·H2O–Ag species mediate coupled electron and proton transfer for catalytic hydride reduction of 4-nitrophenol at the confined nanoscale interface

Abstract: Generally, the catalytic transformation of 4-nitrophenol (4-NP) to 4-aminophenol (4-AP) at heterogeneous metal surface follows a Langmuir-Hinshelwood (L-H) mechanism when sodium borohydride (NaBH4) is used as the sacrificial reductant. Herein,...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 106 publications
0
16
0
Order By: Relevance
“…Thus, the key to the HER with a high activity is to construct surface states to activate the O–H bonds of water and concomitantly promote concerted electron and proton transfer. 37 , 39 , 42 , 47 , 85 Using our model, the micro-kinetics of OER (the strong interaction between O atom of water reactant and SW, suggesting the consumption of surface lattice oxygen at the end of reaction), ORR (the weakening of O–O bond of O 2 by SW), CO 2 RR (the breakage of C–O bonds of CO 2 by SW), and NRR (the weakening of N–N bond of N 2 by SW) can be easily elucidated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the key to the HER with a high activity is to construct surface states to activate the O–H bonds of water and concomitantly promote concerted electron and proton transfer. 37 , 39 , 42 , 47 , 85 Using our model, the micro-kinetics of OER (the strong interaction between O atom of water reactant and SW, suggesting the consumption of surface lattice oxygen at the end of reaction), ORR (the weakening of O–O bond of O 2 by SW), CO 2 RR (the breakage of C–O bonds of CO 2 by SW), and NRR (the weakening of N–N bond of N 2 by SW) can be easily elucidated.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, these results suggested that these identified RDSs are isolated chemical events, while our SW-dominated PBIS model provides solid evidence that interfacial electron transfer, the activation of water (the cleavage of the O–H bond), and the *H combination with proton are synergetic chemical process (or concerted electron and proton transfer process) in high alkaline conditions. Thus, the key to the HER with a high activity is to construct surface states to activate the O–H bonds of water and concomitantly promote concerted electron and proton transfer. ,,,, Using our model, the micro-kinetics of OER (the strong interaction between O atom of water reactant and SW, suggesting the consumption of surface lattice oxygen at the end of reaction), ORR (the weakening of O–O bond of O 2 by SW), CO 2 RR (the breakage of C–O bonds of CO 2 by SW), and NRR (the weakening of N–N bond of N 2 by SW) can be easily elucidated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this is not the case, and isotope labeling experiments with NaBD 4 and D 2 O verified that the hydrogen source of 4-AP counter-intuitively originates from the water solvent, instead of the NaBH 4 reducer. [26][27][28][29] In addition, based on the L-H mechanism, noble metals are necessary because they act as both the adsorption centers of the reaction substrate and the electron transfer medium. 24,[30][31][32][33][34][35][36][37][38][39][40] However, very recently, there have been many examples of catalysts showing that the catalytic efficiency is not only attributed to the metal NPs centers, but also to the microenvironment around the metal catalysts, such as the pH, the type of solvent and the ion additives.…”
Section: Introductionmentioning
confidence: 99%
“…12 Dendritic mesoporous silica nanospheres were modified by immobilizing Pt/Ag NPs to synthesize 4-aminophenol from 4-nitrophenol which follows an interfacial concerted electron-proton transfer mechanism. 13 Anchoring Pd NPs on a nitrogen-doped mesoporous carbon system has been applied in catalytic hydrogenation reactions where pyridinic N atoms were the adsorption sites for Pd NPs in this system. 14 Mesoporous silica with surface thioether functionalization was anchored by Ag NPs for the selective oxidation of C-H bonds of the hydrocarbons to yield their corresponding carbonyl compounds.…”
Section: Introductionmentioning
confidence: 99%